1994
DOI: 10.1097/00006250-199406000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Uterine Hemodynamics With Chemotherapy Response in Gestational Trophoblastic Tumors

Abstract: Uterine hemodynamic characteristics assessed by color Doppler ultrasound might predict and monitor the response to chemotherapy in gestational trophoblastic tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…4, 5). Our observation concurs with that of Long et al [20] and Hsich et al [21] who found that color Doppler ultrasound accurately predicts the chemotherapeutic response in GTD patients. This situation becomes evident when pa tients with a PI of < 1.1 have been found to be more likely to develop drug resistancy [20], It is hypothesized that although serum (3-hCG levels correlate well with the Doppler signals during the various stages of the GTD, there still might be some local factors which produce low diastolic flow detectable by Doppler scanning at the early post-evacutation stage, but escape serum (3-hCG differentiation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…4, 5). Our observation concurs with that of Long et al [20] and Hsich et al [21] who found that color Doppler ultrasound accurately predicts the chemotherapeutic response in GTD patients. This situation becomes evident when pa tients with a PI of < 1.1 have been found to be more likely to develop drug resistancy [20], It is hypothesized that although serum (3-hCG levels correlate well with the Doppler signals during the various stages of the GTD, there still might be some local factors which produce low diastolic flow detectable by Doppler scanning at the early post-evacutation stage, but escape serum (3-hCG differentiation.…”
Section: Discussionsupporting
confidence: 93%
“…This situation becomes evident when pa tients with a PI of < 1.1 have been found to be more likely to develop drug resistancy [20], It is hypothesized that although serum (3-hCG levels correlate well with the Doppler signals during the various stages of the GTD, there still might be some local factors which produce low diastolic flow detectable by Doppler scanning at the early post-evacutation stage, but escape serum (3-hCG differentiation. Our preliminary data may contribute to the potential understanding of why a patient may develop persistent GTD and thus require chemother apy, rather than pinpoint only those who might develop treatment failure [20,21]. This may indicate an avenue for further evaluation, such as those patients who will benefit from prophylactic chemotherapy instituted short ly after termination of a molar pregnancy, evaluating cases of residual uterine tumors [5][6][7][8][9] or replacing angio graphic studies for eliminating lesions of unknown causes detected by other imaging techniques [22], Although the study sample is not large enough to draw any definite conclusions, particularly in relation to persis tent trophoblastic disease, the promising results encour age us to further investigate the contribution that this imaging technique may provide when monitoring pa tients suffering from various GTDs.…”
Section: Discussionmentioning
confidence: 99%
“…9 Color Doppler ultrasound also could offer suggestive clues regarding the tumor histopathology and monitor the efficacy of treatment in trophoblastic tumors. 10,11 However, when color Doppler ultrasound was applied to cervical carcinoma in our previous study, only 46% of cervical tumors showed detectable blood flow signals. 12 With the advantage of relative angle and velocity independence, extended dynamic range, and higher sensitivity, power Doppler ultrasound has been shown to be a useful tumor flow mapping technique.…”
mentioning
confidence: 85%
“…A number of imaging techniques have evolved in recent years: real‐time ultrasound (Fleischer et al 1978; Requard & Mettler 1980; Munyer et al 1981; Woo et al 1985), magnetic resonance imaging (Powell et al 1986), and Doppler ultrasound (Long et al 1990, 1992; Hsieh et al 1994; Chan et al 1994b). All of these noninvasive techniques have been applied in the study of these trophoblastic tumours, with varying success.…”
Section: Discussionmentioning
confidence: 99%